Sosialisasi Perhitungan Kinerja Pelabuhan untuk Karyawan di Lingkungan Pelabuhan Rakyat Paotere - Wihdat Djafar; Misliah Indrus; A. Sitti Chairunnisa; Abd Haris Djalante; Mansyur Hasbullah; M. Rizal Firmansyah; Wahyuddin Wahyuddin; Hamzah Hamzah; Andi Dian Eka Anggriani; Rifkah Fitriah (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Paotere Port is a collection port located in Ujung Tanah District, Makassar City, South Sulawesi. Paotere Port, as one node of the traditional shipping transportation system, is expected to increase its productivity. It needs to be supported by adequate human resources to increase port productivity. One of the activities that can be carried out is training for employees at Paotere Port. Improving HR knowledge and skills in work units, especially port productivity, can benefit the company; besides, this training will benefit employees for promotion. The final target of implementing this socialization is to increase knowledge about the operational performance of ports in general and the operational performance of traditional ports in particular. In addition to knowledge, skills in using performance calculation methods are also expected to be applied by employees. Government regulations guide the material for socialization activities for calculating port operational performance, namely Regulation of the Director General of Sea Transportation Number HK 103/2/18/Djpl-16 concerning performance standards for port operational services at commercially operated ports and Number HK 103/2/2/DJPL -17 concerning guidelines for calculating the performance of port operational services. The operational performance consists of goods and ship service performance. The results of the pre-test and post-test surveys found that employees' understanding of port operational performance increased by 46% after the socialization activities. In the future, employees with a deeper understanding will be beneficial for improving port performance in general and individually benefiting employees in increasing their competencies.